THE EFFECT OF POST-PROCESSING VISUALIZATION ON THE IMAGE QUALITY OF A PANORAMIC DENTAL DIGITAL SYSTEM - HASSAN, LIQAA JABUR (Journal of Duhok University, 2023)
The purpose of this investigation is to quantify and evaluate the diagnostic image quality of dental panoramic radiography with and without post-processing visualization. 72 panoramic photos were analyzed and split into two groups: with post processing and without post processing image. Each picture was given a score based on the subject’s perception of the anatomical zone and features, as well as the density and contrast of the image. According to these specifications, the digital panoramic system that included post-processing received the maximum score of 3.450.19, whereas the digital panoramic system that did not include post-processing received scores of 3.330.33. In conclusion, the use of digital post-processing visualization has the potential to greatly enhance diagnostic quality in terms of contrast and radiographic density